Islamic Law and Customary Law in Contemporary Legal Pluralism in Indonesia: Tension and Constraints - RR Dewi Anggraeni (AHKAM : Jurnal Ilmu Syariah, 2023)
Legal pluralism poses a challenging issue in the application of law in society. Indonesia, as a pluralistic country with diverse ethnicities, customs, and religions, faces conflicts between legal systems. This study addressed the conflicts between Islamic law, state law, and customary law regarding inheritance within the kinship system of Indonesian society. Data were collected from court decisions and legal scholars' opinions, which were then analyzed using the theories of legal pluralism, receptio in complexu, and receptio a contrario. The study found that legal conflicts arise among customary laws within the matrilineal, patrilineal, and parental kinship systems, particularly in inheritance matters. Legal conflicts occur when faced with Islamic law, which resonates with religious practices, and state law, which applies to all citizens. Based on several court decisions, the inheritance distribution resulting from differences in legal systems, especially within the customary kinship system, is disregarded in favor of state and Islamic law. This study implies a shift in the inheritance distribution system, which is no longer purely based on the kinship system of indigenous communities. Keywords: legal pluralism; Islamic law; state law; inheritance distribution AbstrakPluralisme hukum menjadi isu yang menantang dalam penerapan hukum di suatu masyarakat. Indonesia sebagai negara plural yang memiliki perbedaan  suku,  adat,  dan  agama  menghadapi  pertentangan  antar  sistem hukum.  Studi  ini  membahas  pertentangan  hukum  Islam,  hukum  negara dan  hukum  adat  dalam  soal  pembagian  waris  dalam  sistem  kekerabatan masyarakat Indonesia. Data dikumpulkan dari putusan-putusan pengadilan dan  pendapat  para  sarjana  hukum  yang  kemudian  dianalisis  dengan  teori pluralisme  hukum,  teori  receptio in complexu dan teori receptio a contrario. Studi ini menemukan bahwa terjadi konflik hukum antar hukum adat dalam sistem  kekerabatan  matrilineal,  patrilineal,  dan  parental,  khususnya  dalam pembagian waris. Konflik hukum juga terjadi ketika dihadapkan pada hukum Islam yang menjadi afinitas masyarakat dalam beragama dan hukum negara yang menjadi hukum bagi semua warga negara. Berdasarkan sejumlah putusan pengadilan, pembagian waris akibat perbedaan sistem hukum, khususnya dalam sistem  kekerabatan  dalam  hukum  adat  dikesampingkan  dari  hukum  negara dan hukum Islam. Studi ini berimplikasi pada bergesernya sistem pembagian waris yang tidak lagi murni berdasarkan sistem kekerabatan masyarakat adat. Kata Kunci:  pluralisme hukum; hukum Islam; hukum negara; pembagian waris